Output d.c. voltage harmonics research in d.c. contact system of city traction substations - Paianok, O. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Electric measuring devices research technique for traction substations and research results for these substations in Vinnytsia are offered in this work.